Analisis Kecenderungan Cakupan Pemberian Tablet Fe-3 dan Cakupan ANC K4 terhadap Kejadian Komplikasi Kehamilan di Surabaya Tahun 2019: Trends Analysis Scope of Fe-3 Tablet Administration and ANC K4 Activities towards Pregnancy Complications in Surabaya in 2019 - Sukma Arum Sekar Taji; Lucia Yovita Hendrati (Universitas Airlangga, 2023)
Background: Pregnancy complications can occur to the mother and Fetus during pregnancy that can cause illness and even death. The risk factors are non-adherent consumption of iron tablets and irregular Antenatal Care services. Efforts to reduce complications are by providing information about the risk factors of pregnancy and the patient’s location for interventions to the target group. Objectives: This study aimed to map and analyze pregnancy complications based on the scope of iron tablet administration (Fe-3) and ANC K4 in 2019 in Surabaya Methods: This research was a descriptive observational study with a population of 31 sub-districts in Surabaya. It used Spearman’s correlation test to analyze secondary data from the Surabaya City Health Profile in 2019. Creation of distribution maps using Health Mapper 4.3. Results: The distribution map of the scope of Fe-3 tablets administration and ANC K4 activities in Surabaya showed that six sub-districts had low coverage and seven had high coverage. The analysis showed that the relationship between Fe-3 tablet coverage and pregnancy complications was very strong (p=0.001; r=0.985) and positive. In addition, coverage between ANC K4 activity and pregnancy complications was associated with a robust correlation (p=0,001; r=0,982) and a positive direction. Cases of complications occurred throughout the Surabaya area. Conclusions: The scope of Fe-3 tablet administration and ANC K4 activities in 2019 relates to the incidence of pregnancy complications in Surabaya. Most cases of pregnancy complications are in areas with high coverage of iron tablet administration (Fe-3) and ANC K4 activities.